Reaping Richer Returns, Preliminary Overview : Public Spending Priorities for African Agriculture Productivity Growth - Goyal, Aparajita (Washington, DC: World Bank, 2017)
This study is part of the African Regional Studies Program, an initiative of the Africa Region Vice-Presidency at the World Bank. These studies aim to combine high levels of analytical rigor and policy relevance, and to apply them to various topics important for the social and economic development of Sub-Saharan Africa. This book well demonstrates, agricultural spending in Sub-Saharan Africa not only significantly lags behind other developing regions, its impact is also vitiated by subsidy programs and transfers that tend to benefit elites to the detriment of poor people and the agricultural sector itself. Shortcomings of the budgeting processes also reduce spending effectiveness. In light of this scenario, addressing the quality of public spending and the efficiency of resource use becomes an even more important issue than simply addressing the level of spending. The rigorous analysis presented in this book provides options for reform with a view to enhancing investment in the sector and eventually development impact. The evidence show that the efficient use of public funds has been instrumental in laying the foundations f or agricultural productivity growth around the world, providing important lessons for African policymakers and development partners. Investments in rural public goods, combined with better policies and institutions drive agricultural productivity growth. The dividends from investments to strengthen markets, develop and disseminate improved technologies and expand irrigation can be enormous. Similarly, improvement of the policy environment through trade and regulatory policy complements spending by enhancing incentives for producers and innovators to take advantage of public goods, thereby crowding in private investment. Reforming the design and implementation of these subsidy programs while prioritizing government spending in favor of high-return core public goods and policies could produce significant gains. For this reason, this book argues for a rebalancing of the composition of public agricultural spending in order to reap robust development dividends. The authors hope that the findings presented here will resonate with policymakers concerned with agricultural policies, and more specifically with public spending programs that aim to improve the productivity of African agriculture.